Evaluation of the immunogenic properties of the recombinant Histophilus somni outer membrane protein 40 kDa (rOMP40) - Joanna Bajzert; Katarzyna Szydłowska; Paulina Jawor; Adrianna Wawrzyniak; Maciej Pisarek; Tadeusz Stefaniak (BMC Veterinary Research, 2022)
Abstract Background Gram-negative bacterial infections are a serious problem in beef and dairy cattle. Bacterial outer membrane proteins (OMPs) play a pivotal role in cellular survival and the host-bacterium interaction. Histophilus somni OMP40 was identified as a porin with homology between its N-terminal amino acid sequence and the sequences of porins of other gram-negative bacteria The aim of this study was to produce recombinant H. somni OMP40 (rOMP40), optimize its production and evaluate its immunogenic properties in calves. The cross-reactivity of anti-rOMP40 antibodies were also checked. Results The highest overexpression of rOMP40 was demonstrated by Escherichia coli C41 using the autoinduction process. Double immunization of calves (20 μg rOMP40 per animal) induced a significant increase of anti-rOMP40 antibodies in the IgG1 (P ≤ 0.01) and IgG2 (P ≤ 0.01, after first immunization only) subclasses, but not IgM. ELISA revealed increased reactivity of the IgG against surface antigens of E. coli and Pasteurella multocida after the second immunization (P < 0.01). Cross reactivity of anti-rOMP40 antibodies with ~ 40 kDa antigens of most common gram-negative pathogens was shown by Western blotting. Conclusion Immunization with H. somni rOMP40 induced a humoral response in cattle with broad cross-reactivity with similar antigens of other species of Pasteurellaceae and Enterobacteriaceae families and the delayed-type hypersensitivity reaction. The obtained results encourage further study to evaluate the protective effect of the produced protein as a subunit vaccine in cattle.